2009
DOI: 10.1111/j.1440-1746.2008.05604.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐center survey regarding the management of anticoagulation and antiplatelet therapy for endoscopic procedures in Japan

Abstract: There is still a wide variation and confusion among endoscopists after establishment of our national guideline. A robust national guideline with clearer description based on the scientific evidence is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Furthermore, the survey also revealed, interestingly, that personal experience seemed to be a more powerful driver of practice than the published guidelines, even among Western endoscopists. Our multicenter questionnaire in Japan also revealed the low permeation of the Japanese guideline [7], which might be caused by the fact that major parts of these guidelines were established by experts' opinions or limited studies with low evidence level.…”
mentioning
confidence: 93%
“…Furthermore, the survey also revealed, interestingly, that personal experience seemed to be a more powerful driver of practice than the published guidelines, even among Western endoscopists. Our multicenter questionnaire in Japan also revealed the low permeation of the Japanese guideline [7], which might be caused by the fact that major parts of these guidelines were established by experts' opinions or limited studies with low evidence level.…”
mentioning
confidence: 93%
“…We do not have any original written criteria concerning the management of antithrombotic drugs and pre-existing comorbidities. Therefore, the cessation had been principally determined by the doctors who order EGD or who prescribe antithrombotic drugs as in many institutions in Japan [9]. However, they are not necessarily the performers of EGD.…”
Section: Methodsmentioning
confidence: 99%
“…There is no solid evidence, however, to support higher bleeding risk in Asians; several studies reported that no complications related to bleeding were observed in Japanese patients who underwent endoscopic biopsy without cessation of antithrombotic drugs [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the skill level of the endoscopist might affect the bleeding rate, as mentioned in the letter. However, thromboembolic complications sometimes have lethal outcomes, including acute coronary syndrome or cerebral infarction [2,3]. Endoscopists should not put patients at unnecessary thromboembolic risk because of poor training and skills.…”
mentioning
confidence: 99%